Penerapan Strategi Pembelajaran Jigsaw Learning untuk Meningkatkan Hasil Belajar Akidah Akhlak Siswa Tingkat Dasar - Rahmat Rifai Lubis; Nurul Zahriani Jf; Dairina Yusri (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
This study aims to determine student learning outcomes in the Aidah Akhlak lesson in the Final Day material before and after the application of the Jigsaw Learning Learning Strategy for Class V MIS Pendidikan Agama Islam Students. This study uses a classroom action research method consisting of 2 cycles, where each cycle consists of planning , action, observation and reflection. The results of the study explain that (1) The results of student learning before the application of the Jigsaw Learnig learning strategy were from 20 students there was only 1 student who could achieve the KKM score while 19 students were categorized as incomplete. (2) Student learning outcomes in the first cycle of the application of the Jigsaw Learnig learning strategy from the total number of students, namely 20 students, there were only 15 students who could achieve the KKM score while 5 students were categorized as incomplete. (3) Student learning outcomes in the second cycle of the application of the Jigsaw Learnig learning strategy from the total number of students, namely 20 people have completed, and 20 students are in very good grades. Of the 20 people, none were in the good or sufficient and less categories. (4) The students' response to the application of the Jigsaw Learning learning strategy was that they admitted that they were very happy with this method. The reason is that with this method they will not be monotonous just listening to the teacher lecture.